Plectocynipinae, a new subfamily of Figitidae and description of a new Neotropical genus of Thrasorinae (Hymenoptera: Cynipoidea) - Farré, P. Ros; Pujade-Villar, J. (Zootaxa, 2007)
The Thrasorinae (Hymenoptera: Figitidae) has hitherto included 5 genera: Thrasorus, Plectocynips, Pegascynips, Euceroptres and Myrtopsen. They are strongly differentiated into two morphologies: Thrasorus and Myrtopsen, with two metatibial spurs, and Plectocynips and Pegascynips, with only one extremely long metatibial spur. The two latter genera are here removed from Thrasorinae and form the Plectocynipinae n. subf. The fifth genus mentioned, Euceroptres, is removed from Thrasorinae and its affiliations are discussed. A new Neotropical genus, Scutimica n. gen. of Thrasorinae and two new species, Scutimica flava n. sp. collected from Brazil and French Guyana, and S. transcarinata n. sp. collected from Brazil, are described. The validity of Riekcynips is discussed. A key to differentiate the subfamilies of Figitidae and the genera included in Thrasorinae and in Plectocynipinae is also included. Morphological differences are provided and illustrated.